Towards an Integrated Coastal Zone Management in Campania Region (Italy): A Multidisciplinary Approach to the Analysis of Coastal Fishery Activities and their Socio-Economic Management. (10th June 2016) - Gambino, Monica; Accadia, Paolo; Pinello, Dario; Russo, Tommaso; Malvarosa, Loretta; Sabatella, Evelina C.; Cozzolino, Maria; Sabatella, Rosaria F.
Abstract: The paper presents same of the main outcomes of a study concerning the application of the Integrated Coastal Zone Management (ICZM) to Campania region in Italy. The study was focused on the analysis of main uses and activities related to fishery such as the definition of thematic maps describing zones in which fishing activities are prohibited or restricted, areas of distribution of fishing effort, socio economic sustainability of local artisanal fishery, the relevance of fishing tourism and recreational fisheries, an analysis of local fish market. Data provided by official source as the Fishery Data collection, vessel traffic monitoring systems, logbook and legislative sources were successively verified by a field analysis through direct interviews to stakeholders.